2022
DOI: 10.1002/lary.30501
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Reconstruction of the Anterior Skull Base Following Tumor Resection: Application of a Novel Bioabsorbable Plate

Abstract: Objective: Endoscopic repair of skull base defects is required following resection of intracranial pathology via the endoscopic endonasal approach (EEA). Many closure techniques have been described, but choosing between techniques remains controversial. We report outcomes of 560 EEA procedures of skull base reconstruction performed on 508 patients over a 15-year-period. Halfway through this period, we adopted the use of a rigid, bioabsorbable extrasellar plate for reconstruction, enabling a comparison between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…One of the 28 patients (3.7%) developed a postoperative CSF leak; this patient had also undergone a subsequent pterional craniotomy. In 2022, Piscopo et al 11 reviewed outcomes of 560 EETS cases reconstructed with either the RTX, autologous fat graft, DuraGen/GelFoam alone, or nasoseptal flap. Multivariate analysis revealed that RXP was protective against CSF leak compared to other techniques, including autologous grafts or nasoseptal flap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the 28 patients (3.7%) developed a postoperative CSF leak; this patient had also undergone a subsequent pterional craniotomy. In 2022, Piscopo et al 11 reviewed outcomes of 560 EETS cases reconstructed with either the RTX, autologous fat graft, DuraGen/GelFoam alone, or nasoseptal flap. Multivariate analysis revealed that RXP was protective against CSF leak compared to other techniques, including autologous grafts or nasoseptal flap.…”
Section: Discussionmentioning
confidence: 99%
“…Rigid synthetic implants such as the Medpor implant (Stryker; Kalamazoo, MI) [7][8][9] have also been described with favorable results, but carry the risk of implant extrusion and infection over the long term. 10 A technique utilizing a rigid, bioabsorbable plate, the Resorb-X plate (RXP; KLS-Martin, Jacksonville, FL, USA), has previously been reported for reconstruction of the anterior skull base following EETS 11 as well as for reconstruction of skull base defects for CSF rhinorrhea. 12 The primary objective of this study was to examine the incidence and risk factors of developing postoperative CSF leak in patients who underwent EETS for resection of a pituitary adenoma with subsequent use of the RXP as part of a multilayered closure.…”
Section: Introductionmentioning
confidence: 99%
“…No reconstruction or secondary intention Absorbable hemostatic agents (32) Dural sealant (119) Direct suturing "Shoelace" technique (120)(121)(122) Implants or allografts Commercial collagen matrix (123,124) Porcine small intestine submucosa (50,125) Acellular dermal matrix (49,(126)(127)(128) Bovine dura (125) Rigid reconstruction options -"Gasket seal" technique (54)(55)(56) -Bone grafts (27) -Bioabsorbable plates (53) Free autologous grafts Nasal mucosal graft (septum, floor, turbinate) (31,32,(129)(130)(131)(132) Orbital or abdominal fat graft (133,134) Fascia lata graft (135,136) Local rotational flaps Nasoseptal flap (8) Extended nasoseptal flap (137)(138)(139) -Pedicle release (140) Middle turbinate flap (141)(142)(143) Lateral nasal wall flap (35)(36)(37) Anterior ethmoid artery system -Septal flip flap (144) Rhinopharyngeal flap (38,145) Sphenoid mucosal flaps (nonpedicled) (146)<...…”
Section: Technique Examplesmentioning
confidence: 99%
“…Use of rigid skull base reconstruction with bioabsorbable plates or bone grafts to buttress fat graft repairs ("gasket seal") has been studied in several single-institutional retrospective cohorts, with generally excellent outcomes (53)(54)(55)(56)(57) . Piscopo et al…”
Section: Rigid Reconstructionmentioning
confidence: 99%